Ift25 is not a cystic kidney disease gene but is required for early steps of kidney development. (June 2018) - Desai, Paurav B.; San Agustin, Jovenal T.; Stuck, Michael W.; Jonassen, Julie A.; Bates, Carlton M.; Pazour, Gregory J.
Abstract: Eukaryotic cilia are assembled by intraflagellar transport (IFT) where large protein complexes called IFT particles move ciliary components from the cell body to the cilium. Defects in most IFT particle proteins disrupt ciliary assembly and cause mid gestational lethality in the mouse. IFT25 and IFT27 are unusual components of IFT-B in that they are not required for ciliary assembly and mutant mice survive to term. The mutants die shortly after birth with numerous organ defects including duplex kidneys. Completely duplex kidneys result from defects in ureteric bud formation at the earliest steps of metanephric kidney development. Ureteric bud initiation is a highly regulated process involving reciprocal signaling between the ureteric epithelium and the overlying metanephric mesenchyme with regulation by the peri-Wolffian duct stroma. The finding of duplex kidney in Ift25 and Ift27 mutants suggests functions for these genes in regulation of ureteric bud initiation. Typically the deletion of IFT genes in the kidney causes rapid cyst growth in the early postnatal period. In contrast, the loss of Ift25 results in smaller kidneys, which show only mild tubule dilations that become apparent in adulthood. The smaller kidneys appear to result from reduced branching in the developing metanephric kidney. This work indicates that IFT25 and IFT27 are important players in the early development of the kidney and suggest that duplex kidney is part of the ciliopathy spectrum. Highlights: Mutations in Ift25 and Ift27 cause duplex kidney. Unlike other Ift genes, loss of Ift25 from kidney collecting ducts does not cause cyst formation. Loss of Ift25 from kidney collecting ducts results in smaller kidneys with reduced branching.